The Benefits of Belief in God in Mathematics - Haykov, Joseph Mark (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
In this paper, we revisit Blaise Pascal's famous wager and explore its implications for belief in God, particularly through the lens of probability theory. While Pascal's Wager has been widely discussed in philosophical and theological circles, we approach this challenge from a distinctly different perspective. Our backgrounds are in mathematical economics, finance, and computer science, with extensive experience applying mathematics—particularly probability theory—to real-world problems in financial markets, specifically in the domain of statistical arbitrage on Wall Street. Over the past 30 years, we have developed a deep understanding of probability not as an abstract mathematical tool, but as a concrete and practical method for managing uncertainty in financial systems. In this paper, we apply similar probabilistic reasoning to the question of belief in God. Our conclusion can be summarized by an adaptation of the logical principle: "When you have eliminated the impossible, whatever remains, however improbable, must be the truth." — Arthur Conan Doyle, The Sign of the Four